Clinically Undiagnosed Prostate Carcinoma Metastatic to Renal Oncocytoma. (13th June 2012) - Horn, Adam J.; Fritz, Bari E.; LaGrange, Chad A.; West, William W.; Lele, Subodh M.
Abstract : Tumors-to-tumor metastasis is an uncommon occurrence and can be a source of great diagnostic difficulty, especially when the donor tumor is undiagnosed. Here we report a case of a kidney resected for a primary neoplasm (oncocytoma) that harbored metastases from a clinically undiagnosed prostatic adenocarcinoma. The presence of the poorly differentiated metastasis within an otherwise typical oncocytoma in the absence of metastases in the surrounding nonneoplastic renal parenchyma resulted in a diagnostic dilemma. To our knowledge, this is the first report of a case in the English literature of a clinically undiagnosed prostatic adenocarcinoma metastatic to a renal oncocytoma identified on examination of the resected renal neoplasm.